A method for preparing environmentally friendly building materials using industrial solid waste

By combining phosphogypsum with cast steel slag sand, and adding quaternary ammonium salt type long carbon chain polymethylsiloxane and water-based polyurethane prepolymer for modification, an epoxy-modified long carbon chain polymethylsiloxane is formed. Gypsum mortar made of alkanes and water-based polyurethane prepolymers solves the problem of limited application prospects of phosphogypsum in the field of building materials and achieves high value-added utilization and performance improvement.

CN118851710BActive Publication Date: 2025-01-24TIANJIN JUSHI TECH DEV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411351780.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-24
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

As industrial solid waste, phosphogypsum has problems such as high moisture content, strong acidity, complex impurities, moisture resistance and poor water resistance, which limits its effective use in the field of building materials.

Method used

By combining phosphogypsum with cast steel slag sand, and adding quaternary ammonium salt type long carbon chain polymethylsiloxane and water-based polyurethane prepolymer for modification, an epoxy-modified long carbon chain polymethylsiloxane is formed. Gypsum mortar made of alkanes and water-based polyurethane prepolymers improves the moisture-proof performance, mildew resistance and mechanical strength of the material.

Benefits of technology

The high value -added use of phospholpyplasium is realized, improves the moisture -proof, mildew and mechanical properties of building materials, and solves the problem of limited prospects for the application prospects of phosphopide in the field of building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of building materials, specifically a method for preparing environmentally friendly building materials using industrial solid waste. The present invention first reacts 1-undecene and 1,2-epoxy-7-octenes with polymethylhydrogensiloxane, then adds dodecyl dimethyl tertiary amine to react, and obtains quaternary ammonium salt type long carbon chain polymethylsiloxane; then uses polyethylene glycol and isophorone diisocyanate as raw materials to prepare waterborne polyurethane prepolymer; after mixing phosphogypsum, foundry steel slag sand, quaternary ammonium salt type long carbon chain polymethylsiloxane, and waterborne polyurethane prepolymer, water is added and stirred to obtain gypsum mortar; gypsum mortar is cast and formed, and naturally cured after demoulding to obtain environmentally friendly building materials. The building materials prepared by the present invention have good hydrophobicity, mechanical strength and mildew resistance, and also realize the utilization of industrial solid waste phosphogypsum and foundry steel slag sand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a method for preparing environmentally friendly building materials by utilizing industrial solid waste. Background Art

[0002] Phosphoric acid is a common industrial product. In the existing process of producing phosphoric acid, sulfuric acid and apatite are usually used as raw materials, and phosphogypsum is also produced as a by-product in this process. Usually, phosphogypsum is considered to be an industrial solid waste produced in the wet phosphoric acid process. The discharge of phosphogypsum will bring corresponding environmental problems: phosphogypsum enters the ocean in the form of particles, causing excessive heavy metal elements near the Haiyang discharge port, seriously threatening the sustainable function of the surrounding biological communities. The processing, storage and transportation costs of phosphogypsum are huge, so the development and utilization of phosphogypsum is very necessary.

[0003] However, due to the high water content, strong acidity and complex impurities of phosphogypsum, its utilization rate in agriculture, cement production, building materials and soil stabilization is very low; at the same time, as a porous air-hardening material, phosphogypsum has poor moisture resistance and water resistance, which further limits its application prospects in production. Therefore, the high added value and resource utilization of phosphogypsum has become an urgent problem to be solved. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing environmentally friendly building materials using industrial solid waste, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing environmentally friendly building materials using industrial solid waste, comprising the following steps:

[0006] Step 1:

[0007] Dissolve chloroplatinic acid in isopropanol, place in dark for 24 hours, and prepare a chloroplatinic acid-isopropanol solution with a concentration of 0.02-0.03 g / mL; mix 1-undecene and 1,2-epoxy-7-octene to obtain a mixed material; under a nitrogen environment, add the mixed material and polymethyl hydrogen siloxane to tetrahydrofuran, heat to 40-50°C, stir for 10-15 minutes, and then add chloroplatinic acid-isopropanol solution as a catalyst to the reaction system, and catalyze the reaction for 8-10 hours; remove tetrahydrofuran by vacuum distillation to obtain epoxy-modified long carbon chain polymethyl siloxane;

[0008] Step 2:

[0009] Add dodecyl dimethyl tertiary amine to the epoxy-modified long carbon chain polymethylsiloxane, stir and mix, heat to 70-80°C under nitrogen protection, keep warm for 3-4 hours, then add glacial acetic acid to adjust the pH to 4-5, continue to react for 1-2 hours, and finally remove low-boiling substances by vacuum distillation to obtain quaternary ammonium salt-type long carbon chain polymethylsiloxane;

[0010] Step 3:

[0011] The polyethylene glycol is vacuum-dehydrated at 100-120°C, the polyethylene glycol and isophorone diisocyanate are mixed, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 70-80°C, and the temperature is kept for reaction for 1-2 hours; 2,2-dihydroxymethylpropionic acid is added while keeping the temperature, acetone is added to reduce the viscosity, and the reaction is continued for 1-2 hours to obtain a waterborne polyurethane prepolymer;

[0012] Step 4:

[0013] After mixing phosphogypsum, foundry steel slag sand, quaternary ammonium salt type long carbon chain polymethylsiloxane and waterborne polyurethane prepolymer, water is added and stirred evenly to obtain gypsum mortar; the gypsum mortar is cast into shape, and after demolding, it is naturally cured to obtain an environmentally friendly building material.

[0014] Furthermore, in step 1, 1-undecene and 1,2-epoxy-7-octene are mixed in a molar ratio of (2-3):1 to obtain a mixed material.

[0015] Furthermore, in step 1, the mixed material and polymethyl hydrogen siloxane are reacted at a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds of (1.05-1.1):1.

[0016] Furthermore, in step 2, the epoxy group in the epoxy-modified long carbon chain polymethylsiloxane and dodecyldimethyl tertiary amine react in a molar ratio of 1:1.

[0017] Furthermore, in step 3, the weight ratio of polyethylene glycol, isophorone diisocyanate, 2,2-dihydroxymethylpropionic acid and acetone is (42-54):(34-48):(3-5):(5-9).

[0018] Furthermore, in step 4, the amount of each component in the gypsum mortar, by weight, is 80 to 100 parts of phosphogypsum, 50 to 65 parts of foundry steel slag sand, 3 to 5.5 parts of quaternary ammonium salt type long carbon chain polymethylsiloxane, 6 to 8 parts of water-based polyurethane prepolymer, and 8 to 12 parts of water.

[0019] Furthermore, in step 4, the phosphogypsum is hemihydrate phosphogypsum.

[0020] Furthermore, in step 4, the natural curing time after demoulding is 3 to 7 days.

[0021] Furthermore, in step 4, the compressive strength of the environmentally friendly building material is 40-50 MPa; and the flexural strength is 6-10 MPa.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention provides a method for preparing environmentally friendly building materials using industrial solid waste, using phosphogypsum, a byproduct of the phosphoric acid industry, and slag sand produced by the steel casting industry as raw materials to prepare building materials, thereby achieving full utilization of industrial solid waste. In order to improve the moisture resistance, mildew resistance and mechanical strength of the material, the present invention adds quaternary ammonium salt-type long carbon chain polymethylsiloxane and waterborne polyurethane prepolymer to jointly modify the material.

[0023] The preparation method of quaternary ammonium salt type long carbon chain polymethylsiloxane is as follows: 1-undecene and 1,2-epoxy-7-octene are mixed, and then the mixture is subjected to a silylation reaction with the silicon-hydrogen bond on the polymethylhydrogensiloxane, and a long carbon chain and an epoxy group are introduced into the side chain of the polymethylhydrogensiloxane to obtain an epoxy-modified long carbon chain polymethylsiloxane, and the epoxy group is used to react with dodecyl dimethyl tertiary amine to generate hydroxyl groups and quaternary ammonium salts. Among them, the Si-O-Si group in the main chain and the long carbon chain on the side chain are both hydrophobic groups, which provide the material with strong hydrophobic properties. The molecular chain segments containing quaternary ammonium salts are adsorbed on the surface of calcium sulfate dihydrate (CaSO4·2H2O) crystals formed by hydration of phosphogypsum through hydrogen bonds and electrostatic effects; when Aspergillus niger spores invade, the quaternary ammonium root ions will destroy the cell membrane phospholipid bilayer, inactivate the mold spores, and thus produce an anti-fungal effect. The present invention also adds a waterborne polyurethane prepolymer, the terminal group of the polyurethane prepolymer is an isocyanate group, which can react with the hydroxyl group on the quaternary ammonium salt type long carbon chain polymethylsiloxane to form a crosslink, thereby improving the bonding strength between materials in the gypsum mortar. By combining the waterborne polyurethane prepolymer and the quaternary ammonium salt type long carbon chain polymethylsiloxane, the materials are modified together to improve the performance of the materials.

[0024] In addition, it should be noted that although the quaternary ammonium salt segments in the quaternary ammonium salt type long carbon chain polymethylsiloxane show good antibacterial effects, the higher the content, the better. By increasing the content of 1,2-epoxy-7-octene in the mixture, the content of quaternary ammonium salt segments is increased. The experimental results show that too high a quaternary ammonium salt content will lead to a decrease in the performance of the resulting building materials. This is because: According to the colloid theory, during the hydration process of the calcined phosphogypsum, calcium sulfate hemihydrate (CaSO4·0.5H2O) first forms a hydrosol complex with water molecules, and then further forms a gel, and finally transforms into crystalline calcium sulfate dihydrate (CaSO4·2H2O); and the quaternary ammonium salt will be adsorbed on the surface of the calcium sulfate dihydrate formed by hydration; when the quaternary ammonium salt of the side chain of the quaternary ammonium salt type long carbon chain polymethylsiloxane is When the ammonium salt content is low, due to the flexibility of Si-O-Si in the main chain, hydrophobic areas are formed only in the hydrated parts, which will not affect the continued hydration reaction of the incompletely hydrated gel, but the anti-mildew effect is poor at this time; when the quaternary ammonium salt content on the side chain is high, too many quaternary ammonium salt branches are adsorbed on the surface of the crystals formed by hydration, resulting in the fixation of the flexible main chain and the formation of a dense hydrophobic film layer with the long carbon chain of the side chain, which also blocks the incompletely hydrated gel from full contact with water, thereby slowing down or even terminating the hydration process, affecting the hydration effect, and ultimately causing a significant reduction in the strength of the material. In order to take into account the mechanical properties, hydrophobic properties and mildew resistance of the material, the present invention mixes 1-undecene and 1,2-epoxy-7-octene in a molar ratio of (2-3):1, reacts with polymethyl hydrogen siloxane in a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds (1.05-1.1):1, and obtains quaternary ammonium salt type long carbon chain polymethyl siloxane; at the same time, 80-100 parts of phosphogypsum, 50-65 parts of foundry steel slag sand, 3-5.5 parts of quaternary ammonium salt type long carbon chain polymethyl siloxane, 6-8 parts of waterborne polyurethane prepolymer and 8-12 parts of water are mixed according to weight parts to prepare a building material with excellent performance. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Materials and sources used in the present invention: polymethylhydrogensiloxane comes from Zhejiang Chuangji Silicone Materials Co., Ltd., with the product number CJ-1000; polyethylene glycol comes from Jiangsu Hai'an Petrochemical Plant, with the model number PEG-2000; phosphogypsum comes from Anhui Senke New Materials Co., Ltd. Hemihydrate phosphogypsum, with a specific surface area of ​​400-500m 2 / kg; the foundry steel slag sand comes from MCC Baosteel Technical Services Co., Ltd. and is crushed before use, with a particle size of 0.2~0.5mm.

[0027] Example 1: A method for preparing environmentally friendly building materials using industrial solid waste, comprising the following steps:

[0028] Step 1:

[0029] Dissolve chloroplatinic acid in isopropanol, keep it away from light for 24 hours, and prepare a chloroplatinic acid-isopropanol solution with a concentration of 0.03g / mL; mix 1-undecene and 1,2-epoxy-7-octene in a molar ratio of 2:1 to obtain a mixed material; under a nitrogen environment, add the mixed material and polymethylhydrogensiloxane to tetrahydrofuran, heat to 40°C, stir for 10 minutes, and then add chloroplatinic acid-isopropanol solution as a catalyst to the reaction system for catalytic reaction for 8 hours; remove tetrahydrofuran by reduced pressure distillation to obtain epoxy-modified long-chain polymethylsiloxane; wherein the mixed material and polymethylhydrogensiloxane react at a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds of 1.05:1;

[0030] Step 2:

[0031] Add dodecyl dimethyl tertiary amine to the epoxy-modified long carbon chain polymethylsiloxane, stir and mix, heat to 70°C under nitrogen protection, keep warm for 3 hours, then add glacial acetic acid to adjust the pH to 4, continue to react for 1 hour, and finally remove low-boiling substances by reduced pressure distillation to obtain a quaternary ammonium salt type long carbon chain polymethylsiloxane; wherein the epoxy group and dodecyl dimethyl tertiary amine in the epoxy-modified long carbon chain polymethylsiloxane react in a molar ratio of 1:1;

[0032] Step 3:

[0033] The polyethylene glycol was vacuum-dehydrated at 100°C, 48 kg of polyethylene glycol and 37 kg of isophorone diisocyanate were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 70°C, and the temperature was kept for reaction for 1 hour; 4.2 kg of 2,2-dimethylolpropionic acid was added while keeping the temperature, and 7 kg of acetone was added to reduce the viscosity, and the reaction was continued for 1 hour to obtain a waterborne polyurethane prepolymer;

[0034] Step 4:

[0035] 95 kg of phosphogypsum, 55 kg of foundry steel slag sand, 5.5 kg of quaternary ammonium salt type long carbon chain polymethylsiloxane, and 6 kg of waterborne polyurethane prepolymer were mixed, and 10 kg of water was added and stirred evenly to obtain gypsum mortar; the gypsum mortar was cast and formed, and naturally cured for 3 days after demolding to obtain an environmentally friendly building material.

[0036] Embodiment 2: A method for preparing environmentally friendly building materials using industrial solid waste, comprising the following steps:

[0037] Step 1:

[0038] Dissolve chloroplatinic acid in isopropanol, place in dark for 24 hours, and prepare a chloroplatinic acid-isopropanol solution with a concentration of 0.03 g / mL; mix 1-undecene and 1,2-epoxy-7-octene in a molar ratio of 2.5:1 to obtain a mixed material; add the mixed material and polymethyl hydrogen siloxane to tetrahydrofuran under a nitrogen environment, heat to 45°C, stir for 13 minutes, and then add chloroplatinic acid-isopropanol solution as a catalyst to the reaction system for 9 hours of catalytic reaction; remove tetrahydrofuran by reduced pressure distillation to obtain epoxy-modified long carbon chain polymethyl siloxane; wherein the mixed material and polymethyl hydrogen siloxane react at a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds of 1.05:1;

[0039] Step 2:

[0040] Add dodecyl dimethyl tertiary amine to the epoxy-modified long carbon chain polymethylsiloxane, stir and mix, heat to 75°C under nitrogen protection, keep warm for 3.5 hours, then add glacial acetic acid to adjust the pH to 4.5, continue to react for 1.5 hours, and finally remove low-boiling substances by reduced pressure distillation to obtain quaternary ammonium salt type long carbon chain polymethylsiloxane; wherein the epoxy group and dodecyl dimethyl tertiary amine in the epoxy-modified long carbon chain polymethylsiloxane react in a molar ratio of 1:1;

[0041] Step 3:

[0042] The polyethylene glycol was vacuum-dehydrated at 110°C, 48 kg of polyethylene glycol and 37 kg of isophorone diisocyanate were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 75°C, and the reaction was kept warm for 1.5 hours; 4.2 kg of 2,2-dimethylolpropionic acid was added while keeping warm, and 7 kg of acetone was added to reduce the viscosity, and the reaction was continued for 1.5 hours to obtain a waterborne polyurethane prepolymer;

[0043] Step 4:

[0044] 95 kg of phosphogypsum, 55 kg of foundry steel slag sand, 5.5 kg of quaternary ammonium salt type long carbon chain polymethylsiloxane, and 7 kg of waterborne polyurethane prepolymer were mixed, and 10 kg of water was added and stirred evenly to obtain gypsum mortar; the gypsum mortar was cast into shape, and naturally cured for 5 days after demolding to obtain an environmentally friendly building material.

[0045] Embodiment 3: A method for preparing environmentally friendly building materials using industrial solid waste, comprising the following steps:

[0046] Step 1:

[0047] Dissolve chloroplatinic acid in isopropanol, place in dark for 24 hours, and prepare a chloroplatinic acid-isopropanol solution with a concentration of 0.03 g / mL; mix 1-undecene and 1,2-epoxy-7-octene in a molar ratio of 3:1 to obtain a mixed material; add the mixed material and polymethyl hydrogen siloxane to tetrahydrofuran under a nitrogen environment, heat to 50°C, stir for 15 minutes, and then add chloroplatinic acid-isopropanol solution as a catalyst to the reaction system for 10 hours of catalytic reaction; remove tetrahydrofuran by reduced pressure distillation to obtain epoxy-modified long carbon chain polymethyl siloxane; wherein the mixed material and polymethyl hydrogen siloxane react at a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds of 1.05:1;

[0048] Step 2:

[0049] Add dodecyl dimethyl tertiary amine to the epoxy-modified long carbon chain polymethylsiloxane, stir and mix, heat to 80°C under nitrogen protection, keep warm for 4 hours, then add glacial acetic acid to adjust the pH to 5, continue to react for 2 hours, and finally remove low-boiling substances by reduced pressure distillation to obtain a quaternary ammonium salt type long carbon chain polymethylsiloxane; wherein the epoxy group and dodecyl dimethyl tertiary amine in the epoxy-modified long carbon chain polymethylsiloxane react in a molar ratio of 1:1;

[0050] Step 3:

[0051] The polyethylene glycol was vacuum-dehydrated at 120°C, 48 kg of polyethylene glycol and 37 kg of isophorone diisocyanate were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 80°C, and the mixture was kept warm for 2 hours; 4.2 kg of 2,2-dimethylolpropionic acid was added while keeping warm, 7 kg of acetone was added to reduce the viscosity, and the reaction was continued for 2 hours to obtain a waterborne polyurethane prepolymer;

[0052] Step 4:

[0053] 95 kg of phosphogypsum, 55 kg of foundry steel slag sand, 5.5 kg of quaternary ammonium salt type long carbon chain polymethylsiloxane, and 8 kg of waterborne polyurethane prepolymer were mixed, and 10 kg of water was added and stirred evenly to obtain gypsum mortar; the gypsum mortar was cast and formed, and naturally cured for 7 days after demolding to obtain an environmentally friendly building material.

[0054] Comparative Example 1: No quaternary ammonium salt type long carbon chain polymethylsiloxane was added, and other parameters were the same as those in Example 1.

[0055] Step 1:

[0056] The polyethylene glycol was vacuum-dehydrated at 100°C, 48 kg of polyethylene glycol and 37 kg of isophorone diisocyanate were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 70°C, and the temperature was kept for reaction for 1 hour; 4.2 kg of 2,2-dimethylolpropionic acid was added while keeping the temperature, and 7 kg of acetone was added to reduce the viscosity, and the reaction was continued for 1 hour to obtain a waterborne polyurethane prepolymer;

[0057] Step 2:

[0058] 95 kg of phosphogypsum, 55 kg of foundry steel slag sand, and 6 kg of waterborne polyurethane prepolymer were mixed, and 10 kg of water was added and stirred evenly to obtain gypsum mortar; the gypsum mortar was cast into shape, and naturally cured for 3 days after demolding to obtain an environmentally friendly building material.

[0059] Comparative Example 2: No waterborne polyurethane prepolymer was added, and the other parameters were the same as those in Example 2.

[0060] Step 1:

[0061] Dissolve chloroplatinic acid in isopropanol, place in dark for 24 hours, and prepare a chloroplatinic acid-isopropanol solution with a concentration of 0.03 g / mL; mix 1-undecene and 1,2-epoxy-7-octene in a molar ratio of 2.5:1 to obtain a mixed material; add the mixed material and polymethyl hydrogen siloxane to tetrahydrofuran under a nitrogen environment, heat to 45°C, stir for 13 minutes, and then add chloroplatinic acid-isopropanol solution as a catalyst to the reaction system for 9 hours of catalytic reaction; remove tetrahydrofuran by reduced pressure distillation to obtain epoxy-modified long carbon chain polymethyl siloxane; wherein the mixed material and polymethyl hydrogen siloxane react at a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds of 1.05:1;

[0062] Step 2:

[0063] Add dodecyl dimethyl tertiary amine to the epoxy-modified long carbon chain polymethylsiloxane, stir and mix, heat to 75°C under nitrogen protection, keep warm for 3.5 hours, then add glacial acetic acid to adjust the pH to 4.5, continue to react for 1.5 hours, and finally remove low-boiling substances by reduced pressure distillation to obtain quaternary ammonium salt type long carbon chain polymethylsiloxane; wherein the epoxy group and dodecyl dimethyl tertiary amine in the epoxy-modified long carbon chain polymethylsiloxane react in a molar ratio of 1:1;

[0064] Step 3:

[0065] 95 kg of phosphogypsum, 55 kg of foundry steel slag sand, and 5.5 kg of quaternary ammonium salt type long carbon chain polymethylsiloxane were mixed, and 10 kg of water was added and stirred evenly to obtain gypsum mortar; the gypsum mortar was cast into shape, and naturally cured for 5 days after demolding to obtain an environmentally friendly building material.

[0066] Comparative Example 3: The content of 1,2-epoxy-7-octene in the mixed material was increased, and the other parameters were the same as those in Example 3.

[0067] Step 1:

[0068] Dissolve chloroplatinic acid in isopropanol, keep it away from light for 24 hours, and prepare a chloroplatinic acid-isopropanol solution with a concentration of 0.03g / mL; mix 1-undecene and 1,2-epoxy-7-octene in a molar ratio of 1:3 to obtain a mixed material; under a nitrogen environment, add the mixed material and polymethyl hydrogen siloxane to tetrahydrofuran, heat to 50°C, stir for 15 minutes, and then add chloroplatinic acid-isopropanol solution as a catalyst to the reaction system, and catalyze the reaction for 10 hours; remove tetrahydrofuran by reduced pressure distillation to obtain epoxy-modified long-chain polymethyl siloxane; wherein the mixed material and polymethyl hydrogen siloxane react at a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds of 1.05:1;

[0069] Step 2:

[0070] Add dodecyl dimethyl tertiary amine to the epoxy-modified long carbon chain polymethylsiloxane, stir and mix, heat to 80°C under nitrogen protection, keep warm for 4 hours, then add glacial acetic acid to adjust the pH to 5, continue to react for 2 hours, and finally remove low-boiling substances by reduced pressure distillation to obtain a quaternary ammonium salt type long carbon chain polymethylsiloxane; wherein the epoxy group and dodecyl dimethyl tertiary amine in the epoxy-modified long carbon chain polymethylsiloxane react in a molar ratio of 1:1;

[0071] Step 3:

[0072] The polyethylene glycol was vacuum-dehydrated at 120°C, 48 kg of polyethylene glycol and 37 kg of isophorone diisocyanate were mixed, dibutyltin dilaurate was used as a catalyst, the temperature was raised to 80°C, and the mixture was kept warm for 2 hours; 4.2 kg of 2,2-dimethylolpropionic acid was added while keeping warm, 7 kg of acetone was added to reduce the viscosity, and the reaction was continued for 2 hours to obtain a waterborne polyurethane prepolymer;

[0073] Step 4:

[0074] 95 kg of phosphogypsum, 55 kg of foundry steel slag sand, 5.5 kg of quaternary ammonium salt type long carbon chain polymethylsiloxane, and 8 kg of waterborne polyurethane prepolymer were mixed, and 10 kg of water was added and stirred evenly to obtain gypsum mortar; the gypsum mortar was cast and formed, and naturally cured for 7 days after demolding to obtain an environmentally friendly building material.

[0075] Comparative Example 4: The quaternary ammonium salt type long carbon chain polymethylsiloxane and the waterborne polyurethane prepolymer were not added, and the other parameters were the same as those in Example 3.

[0076] 95 kg of phosphogypsum and 55 kg of foundry steel slag sand were mixed, and 10 kg of water was added and stirred evenly to obtain gypsum mortar; the gypsum mortar was cast into shape, and naturally cured for 7 days after demolding to obtain an environmentally friendly building material.

[0077] Experiment: The performance of the environmentally friendly building materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was tested. The environmentally friendly building materials used in the test were made into samples with a size of 40 mm×40 mm×160 mm. The experimental test method is as follows.

[0078] Antifungal performance test: The experimental instruments, culture medium and samples were sterilized by steam sterilization at 120°C for 30 min. Aspergillus niger spores were inoculated on potato-glucose culture medium. After 7 days of culture, the mold spores on the surface of the culture medium were scraped with sterile water and an inoculation loop. After oscillation dispersion, filtration, centrifugation and dilution, Aspergillus niger spore suspension was obtained. The spore concentration of the suspension was determined using a hemocytometer and adjusted to 0.8×10 6 ~1.2×10 6 The Aspergillus niger spore suspension was evenly sprayed on the sample surface, and the sample was placed in a constant temperature and humidity curing box at 28°C and 90% humidity for 14 days to observe the mildew on the sample surface and inside.

[0079] Mechanical strength test: According to the national standard GB / T 17669.3-1999, the samples were tested using a fully automatic compression and flexural testing machine. The loading rates of the compressive strength and flexural strength tests were 2400N / S and 50N / S respectively.

[0080] Hydrophilicity and hydrophobicity test: A contact angle meter was used to detect the hydrophilicity and hydrophobicity of the sample surface, and the volume of the pure water droplet was 10 μL.

[0081] The experimental results are shown in Table 1:

[0082] Table 1. Test results of various properties of environmentally friendly building materials

[0083]

[0084] Conclusion: Comparative Example 4 is a blank control group. By comparing it with Examples 1 to 3, it can be seen that after adding quaternary ammonium salt-type long carbon chain polymethylsiloxane and waterborne polyurethane prepolymer in Examples 1 to 3, the antifungal performance, mechanical strength and hydrophobicity of the samples are improved; while the antifungal performance of the sample in Comparative Example 4 is poor, and the surface of the material shows super hydrophilicity. The data of Example 1 and Comparative Example 1 show that quaternary ammonium salt-type long carbon chain polymethylsiloxane can enhance the antifungal performance and hydrophobicity of the sample; the data of Example 2 and Comparative Example 2 show that the addition of waterborne polyurethane prepolymer can improve the mechanical strength of the material; the data of Example 3 and Comparative Example 3 show that increasing the content of 1,2-epoxy-7-octene in the mixture will lead to more quaternary ammonium salt grafted on quaternary ammonium salt-type long carbon chain polymethylsiloxane, and the quaternary ammonium salt produces an adsorption effect with the CaSO4·2H2O crystals formed by hydration, forming a hydrophobic film on the surface of the crystal, and affecting the hydration reaction process of the unhydrated part, resulting in a decrease in the mechanical strength of the material.

[0085] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing environmentally friendly building materials using industrial solid waste, characterized in that: 80-100 parts by weight of phosphogypsum, 50-65 parts of foundry steel slag sand, 3-5.5 parts of quaternary ammonium salt type long carbon chain polymethylsiloxane, and 6-8 parts of waterborne polyurethane prepolymer are mixed, and 8-12 parts of water are added and stirred evenly to obtain gypsum mortar; the gypsum mortar is cast and formed, and naturally cured after demoulding to obtain an environmentally friendly building material; Wherein, the preparation method of quaternary ammonium salt type long carbon chain polymethylsiloxane comprises the following steps: Step 1: dissolving chloroplatinic acid in isopropanol, keeping it away from light for 24 hours, and preparing a chloroplatinic acid-isopropanol solution with a concentration of 0.02-0.03 g / mL; mixing 1-undecene and 1,2-epoxy-7-octene to obtain a mixed material; adding the mixed material and polymethylhydrogensiloxane to tetrahydrofuran under a nitrogen environment, heating to 40-50° C., stirring for 10-15 minutes, and then adding chloroplatinic acid-isopropanol solution as a catalyst to the reaction system, and catalyzing the reaction for 8-10 hours; removing tetrahydrofuran by vacuum distillation to obtain epoxy-modified long carbon chain polymethylsiloxane; the mixed material is obtained by mixing 1-undecene and 1,2-epoxy-7-octene in a molar ratio of (2-3):1; Step 2: Add dodecyldimethyl tertiary amine to the epoxy-modified long-chain polymethylsiloxane, stir and mix, heat to 70-80°C under nitrogen protection, keep warm for 3-4 hours, then add glacial acetic acid to adjust the pH to 4-5, continue to react for 1-2 hours, and finally remove low-boiling substances by reduced pressure distillation to obtain quaternary ammonium salt-type long-chain polymethylsiloxane.

2. The method for preparing environmentally friendly building materials using industrial solid waste according to claim 1, characterized in that: In step 1, the mixed material and polymethyl hydrogen siloxane are reacted at a molar ratio of carbon-carbon double bonds to silicon-hydrogen bonds (1.05-1.1):

1.

3. The method for preparing environmentally friendly building materials using industrial solid waste according to claim 1, characterized in that: In step 2, the epoxy group in the epoxy-modified long carbon chain polymethylsiloxane reacts with dodecyldimethyl tertiary amine in a molar ratio of 1:

1.

4. The method for preparing environmentally friendly building materials using industrial solid waste according to claim 1, characterized in that: The preparation method of the waterborne polyurethane prepolymer is as follows: vacuum dehydrating polyethylene glycol at 100-120° C., mixing polyethylene glycol and isophorone diisocyanate, using dibutyltin dilaurate as a catalyst, heating to 70-80° C., and keeping the temperature for reaction for 1-2 hours; adding 2,2-dihydroxymethylpropionic acid while keeping the temperature, adding acetone to reduce the viscosity, and continuing the reaction for 1-2 hours to obtain a waterborne polyurethane prepolymer.

5. The method for preparing environmentally friendly building materials using industrial solid waste according to claim 4, characterized in that: The weight ratio of polyethylene glycol, isophorone diisocyanate, 2,2-dihydroxymethylpropionic acid and acetone is (42~54):(34~48):(3~5):(5~9).

6. The method for preparing environmentally friendly building materials using industrial solid waste according to claim 1, characterized in that: Phosphogypsum is hemihydrate phosphogypsum; the natural curing time after demoulding is 3 to 7 days; the environmentally friendly building material has a compressive strength of 40 to 50 MPa; and a flexural strength of 6 to 10 MPa.

Citation Information

Patent Citations

  • Anti-mildew water-resistant beta-type building phosphogypsum self-leveling mortar and preparation method thereof

    CN116082013A

  • Antibacterial polyurethane and preparation method thereof

    CN116751352A

  • Synthesis method of reticular long-carbon-chain siloxane and phosphogypsum-based material with hydrophobic function

    CN117069944A

  • Organic silicon emulsion and preparation method thereof

    CN118273127A